Analisis Keamanan Website SMA Negeri 2 Sumbawa Besar Menggunakan Metode Penetration Testing (Pentest) - Yudi Mulyanto; Mohammad Taufan Asri Zaen; Yuliadi Yuliadi; Safwan Sihab (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Website security is becoming a very important aspect along with the increasing volume of data exchanged on the internet. High School 2 Sumbawa Besar provides information on a website, both information for school introductions or information related to schools can be through several media. Some time ago the school's website was attacked by information criminals who caused the appearance of the website to change and steal some important school data. Weak website security systems can be easy targets for cyber criminals. They know various ways to get into the website security system and perform various actions that can harm the organization. Based on the conditions that occurred on the school's website, a research was conducted to analyze the level of security and look for loopholes in the weaknesses of the High School 2 Sumbawa Besar website. In this analysis, researchers tested the school's website using the Penetration Testing method. Test is carried out in several stages, namely Footprinting, Scanning Fingerprinting, Exploit and Reporting. The process of testing the website security of High School 2 Sumbawa Besar found several loopholes that detected 13 sub-file vulnerabilities with low and medium status. Results of this study are the results of security testing in the form of a list of vulnerabilities that can be a recommendation for the school in improving website security.